Artificial Intelligence-Based Assessment Training to Improve Teacher Competence - Ike Lusi Meilina; Maryani Maryani; Ernasari Ernasari; Adinda Citra Badarsila; Rojabita Dwirgahayu Nurhidayat; Aditya Kurniawan (Yayasan Keluarga Guru Mandiri, 2026)
The integration of technology, particularly Artificial Intelligence (AI), into learning assessment plays a pivotal role in improving the effectiveness of education. However, the digital competence gap has caused teachers at MTs. Hidayatul Mubtadi’in Jember will still predominantly use conventional assessments. This community service program aims to improve teachers’ professional competencies in designing AI-based assessment instruments. The implementation method combines the development of 4D model materials (Define, Design, Develop, Disseminate) with Direct Instruction and Cooperative Learning model training, which 22 teachers followed. The evaluation instruments included an AI assessment guidebook validation sheet, competency tests, and participant satisfaction questionnaires. The results of the activity show that the developed AI Assessment Guidebook is valid, with a score of 82.00. The effectiveness of the training is evident from the high level of participant understanding, with an average post-test score of 88.67 and a participant satisfaction rating of 89.56 (Very Good). Implicitly, this training significantly contributed to developing teacher competency, as participants can now independently create a variety of questions and assessment rubrics using AI. This program recommends continuous technological adaptation to support the digital madrasah (Islamic school) ecosystem.